PENDUGAAN MODEL VOLUME POHON BERDIRI TANAMAN JATI (Tectona grandis L.f) UMUR 10 TAHUN (Studi Lahan Jati Universitas Merdeka Madiun) - Dwi Arief Putra, Mochammad; Lukito, Martin (JURNAL AGRI-TEK, 2016)
The collection of information about the potential these stands inextricably linked to the measurement of the volume of timber, either directly or indirectly. For interpretation timber volume inventarsisasi forest activities can be used with an auxiliary table that is practical. The purpose of this study to determine the volume of the stand either manually or using the model to determine the ratio of the volume results. Data were collected by census intensity of 100% at the campus garden land Merdeka Madiun University. To suspect standing stock volume by measuring the diameter (dbh) and tree height. Then from the results data created table manually and table models to determine the result of the difference in the two tables, model estimation elected is Power is with the equation Y = 16,700 x 2,608 dbh (m), with R2 0.944 (RSS) 0.758 SEE 0.951 after it tested test if the t value is smaller than the value of the table then it means there is no significant effect between manual calculations and model calculations.Keywoords : Standingstock, Volume, Model allometric